Astrocyte tissue factor controls CNS hemostasis and autoimmune inflammation. Issue 141 (May 2016) - Wang, Shaobin; Reeves, Brandi; Pawlinski, Rafal
Abstract: Tissue factor is the primary initiator of the coagulation cascade. Formation of the TF:FVIIa complex activates both FX and FIX, with subsequent thrombin generation, fibrin deposition and activation of platelets. In addition to playing important role in hemostasis and thrombosis, TF and downstream coagulation proteases can mediate intracellular signaling via activation of protease-activated receptors (PARs). Maintaining hemostasis in the brain is of utmost importance: bleeding or thrombosis within this organ can lead to significant morbidity and mortality. Both TF and PARs are widely expressed within the CNS, with TF expressed predominantly by astrocytes and PARs expressed in multiple cell types including astrocytes, neurons, microglia and oligodendrocytes [1–4 ]. PARs activation can result in either neuronal survival or death and link the coagulation system with the inflammatory response. In this brief review we summarize the contribution of the coagulation system to brain hemostasis as well as to the pathophysiology of stroke and multiple sclerosis.